Novel fluoroalkyl end-capped amphiphilic diblock copolymers with pH/temperature response and self-assembly behavior - Zhang, Hu (Langmuir : the ACS journal of surfaces and colloids, 2008)
A series of fluoroalkyl end-capped diblock copolymers of poly[2-(N,N-dimethylamino)ethyl methacrylate] (PDMAEMA or PDMA) and poly[2-(N,N-diethylamino)ethyl methacrylate] (PDEAEMA or PDEA) have been synthesized via oxyanion-initiated polymerization, in which a potassium alcoholate of 4,4,5,5,6,6,7,7,7-nonafluoro-1-heptanol (NFHOK) was used as an initiator. The chemical structures of the NFHO-PDMA-b-PDEA and NFHO-PDEA-b-PDMA depended on the addition sequence of the two monomers and the feeding molar ratios of [DMA] to [DEA] during the polymerization process. These copolymers have been characterized by (1)H NMR and (19)F NMR spectroscopy and gel permeation chromatography (GPC). The aggregation behavior of these copolymers in aqueous solutions at different pH media was studied using a combination of surface tension, fluorescence probe, and transmission electron microscopy (TEM). Both diblock copolymers exhibited distinct pH/temperature-responsive properties. The critical aggregation concentrations (cacs) of these copolymers have been investigated, and the results showed that these copolymers possess excellent surface activity. Besides, these fluoroalkyl end-capped diblock copolymers showed pH-induced lower critical solution temperatures (LCSTs) in water. TEM analysis indicated that the NFHO-PDMA(30)-b-PDEA(10) diblock copolymers can self-assemble into the multicompartment micelles in aqueous solutions under basic conditions, in which the pH value is higher than the pKa values of both PDMA and PDEA homopolymers, while the NFHO-PDEA(10)-b-PDMA(30) diblock copolymers can form flowerlike micelles in basic aqueous solution